A soft robot structure with limbless resonant, stick and slip locomotion. (23rd September 2019) - Calabrese, Luigi; Berardo, Alice; De Rossi, Danilo; Gei, Massimiliano; Pugno, Nicola Maria; Fantoni, Gualtiero
Abstract: We present a smart robot structure that exploits anisotropic friction to achieve stick-slip locomotion. The robot is made out of three components: a plastic beam, a planar dielectric elastomer actuator and four bristle pads with asymmetric rigid metallic bristles. We show that when the robot is electronically activated at increasing frequency, its structure exploits the resonance condition to reach the maximum locomotion speed. The fundamental frequency of the structure is estimated both analytically and numerically, allowing the range of frequencies in which the top locomotion speed was observed during the experiments to be identified. The locomotion speed of the robot as a function of the actuation frequency is estimated with a frequency response analysis performed on a discretised model of the structure, revealing good agreement with the experimental evidence.